PENGARUH PRODUK DAN LOKASI TERHADAP MINAT MENABUNG MASYARAKAT DI BANK SYARIAH INDONESIA KCP POLEWALI - Nurfitriani; Ulfa Hidayati (Institut Agama Islam Negeri Parepare, 2021)
Banks can be the people's choice in terms of saving for daily or future needs. The Muslim community can choose a seat that does not conflict with their Islamic teachings.